Yield and Production Gaps in Rainfed Wheat, Barley, and Canola in Alberta - Chapagain, Tejendra; Good, Allen (Frontiers in Plant Science, 2015)
Improving crop yields are essential to meet the increasing pressure of global food demands. The loss of high quality land, the slowing in annual yield increases of major cereals, increasing fertilizer use, and the effect of this on the environment all indicate that we need to develop new strategies to increase grain yields with less impact on the environment. One strategy that could help address this concern is by narrowing the yield gaps of major crops using improved genetics and management. The objective of this study was to determine wheat (Triticum spp. L.), barley (Hordeum vulgare L.), and canola (Brassica napus L.) yields and production gaps in Alberta. We used ten years of data (2005-14) to understand yield variability and input efficiency at a farmers’ specified level of management, and the yield potential under optimal management to suggest appropriate pathways for closing yield gaps. Significant management gaps were observed between attainable and actual yields of rainfed wheat (24%), barley (25%), and canola (30%). In addition, genetic gaps (i.e., gaps due to genetic selection) in wheat, barley, and canola were 18%, 12%, and 5%, respectively. Genetic selection with optimal crop management could increase yields of wheat, barley, and canola significantly, with estimated yield gains of 3.42, 1.92, and 1.65 million tonnes, respectively, each year under rainfed conditions in Alberta. This paper identifies yield gaps and offers suggestions to improve efficiency in crop production.